Uterine Microbiota of Dairy Cows With Clinical and Subclinical Endometritis - Wang, Meng-Ling; Liu, Ming-Chao; Xu, Jin; An, Li-Gang; Wang, Jiu-Feng; Zhu, Yao-Hong (Frontiers in Microbiology, 2018)
The objective of this study was to characterize the uterine microbiota of dairy cows with clinical and subclinical endometritis and to identify the potential bacterial genera as well as their interactions associated with uterine disease. Uterine flush samples (n = 27) were collected from 13 healthy, 5 subclinical endometritic (SE), and 9 clinical endometritic (CE) cows at 30 days postpartum. Microbial DNA from uterine flush samples was subjected to sequencing of the 16S rRNA gene on the Illumina MiSeq platform. The uterine microbiota of healthy, SE, and CE cows had similarly complex microbial diversity, and shared 293 of 445 operational taxonomic units. Uterine microbiota harbored similar level microbial diversity and richness, and shared most bacterial species in all cows. However, endometritic and healthy cows could be discriminated by the relative abundance of bacterial genera. In CE cows, uterine microbiota was characterized characteristic by increased abundance of Fusobacterium and unique presence of Trueperella and Peptoniphilus, suggesting these genera may play crucial roles in the pathogenesis of clinical endometritis. For SE cows, known intrauterine pathogens were almost absent and uterine microbiota was characterized by enrichment of Lactobacillus and Acinetobacter. In uterine microbiota of SE cows, common pathogens were almost absent. Compared with healthy cows, Arthrobacter, Carnobacterium, Psychrobacter, Lactobacillus, Oceanobacillus, and Acinetobacter were enriched in the uterine microbiota of SE cows, indicating that these genera were associated with the development of subclinical endometritis. Analysis of correlations between bacterial genera showed that the uterine microbiota exhibited two co-occurrence groups (i.e. the Lactococcus and the Fusobacterium COGs), indicating that the synergistic effect by co-occurred bacteria may be an important aspect of pathogenesis.indicating that uterine microbiota is composed of cooperative groups with synergistic effects. Our findings support that common uterine pathogens are not associated with subclinical endometritis at 30 days postpartum and indicate the need of investigating the role of commensal bacteria such as Lactobacillus, and Acinetobacter in the inflammatory process of uterine endometrium.